TINJAUAN SUSPEN, SURPRISE, DAN NILAI MORAL DALAM KISAH “CERITA TAK BERUJUNG” KARYA ABDUL AZIZ ABDUL MAJID - Alamsyah, Teuku; Taib, Rostina; Armia, Armia; Nurrahmah, Nurrahmah (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
This study aims to describe suspense, surprise, and moral values in the story “Cerita Tak Berujung” by Abdul Aziz Abdul Majid (2002). The data source of this research is